A global ocean state estimation using tidally induced vertical-mixing schemes. (November 2022) - Osafune, Satoshi; Kouketsu, Shinya; Doi, Toshimasa; Sugiura, Nozomi; Masuda, Shuhei
Abstract: We updated the Estimated STate of the global Ocean for Climate research (ESTOC), a long-term ocean state estimation dataset that includes physical and biogeochemical fields. The physical field is optimized through a data synthesis experiment using a quasi-global four-dimensional variational data assimilation system, and under the optimized physical field, the biogeochemical field is optimized by using a Green's function. To improve the reliability of the dynamics reproduced in the model, we implemented tidally induced turbulent mixing schemes and geothermal heat flux. This paper provides an overview of the assimilation system with an emphasis on updated elements and including details of the mixing schemes and presents preliminary results focusing on the warming in the abyssal ocean (below 3000 m) using this updated ESTOC published as Version 04a. The reproduction of both the climatological state and temporal change in abyssal-water properties is, on the whole, improved in this updated ESTOC in comparison with a previous version. This improved reproduction of the abyssal ocean state with the refined physical processes that play major roles in determining abyssal-water properties makes our new synthesized dataset valuable, at least for understanding the abyssal ocean. In this updated ESTOC, the abyssal-water warming results from a near-steady imbalance between the heating effect due to vertical diffusion and geothermal flux, and the cooling effect by advection and horizontal diffusion in the North Pacific, suggesting that the warming occurs over a long timescale. We also show that the downward heat flux related to bottom-intensified vertical mixing near the generation site of the internal tide plays an important role in determining the improved distribution of abyssal-water warming in the Pacific Ocean. These results suggest the importance of using knowledge of vertical mixing as a priori information in ocean state estimation. Highlights: Tidal mixing schemes are implemented in a global ocean data assimilation system. A data synthesis experiment is conducted to obtain a long-term ocean state estimation. The assimilated model reproduces the deep ocean state including bottom-water warming. Bottom-intensified tidal mixing plays an important role in warming in the model.